Pathophysiology of Thrombosis in Peripheral Artery Disease - Habib, Aida; Petrucci, Giovanna; Rocca, Bianca (Current Vascular Pharmacology, 2020)
Under physiological conditions, peripheral arteries release endogenous vascular-protective and antithrombotic agents. Endothelial cells actively synthesize vasoactive mediators, which regulate vascular tone and platelet reactivity thus preventing thrombosis. Atherosclerosis disrupts homeostasis and favours thrombosis by triggering pro-thrombotic responses in the vessels, platelet activation, aggregation as well as vasoconstriction, phenomena that ultimately lead to symptomatic lumen restriction or complete occlusion. In the present review, we will discuss the homeostatic role of arterial vessels in releasing vascular-protective agents, such as nitric oxide and prostacyclin, the role of pro- and anti-thrombotic vascular receptors as well as the contribution of circulating platelets and coagulation factors in triggering the pro-thrombotic response(s). We will discuss the pathological consequences of disrupting the protective pathways in the arteries and the pharmacological interventions along these pathways.
Keywords: VSM